2010
DOI: 10.1118/1.3519903
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of scatter rejection and low‐contrast performance of scan equalization digital radiography (SEDR), slot‐scan digital radiography, and full‐field digital radiography systems for chest phantom imaging

Abstract: Purpose: To investigate and compare the scatter rejection properties and low-contrast performance of the scan equalization digital radiography ͑SEDR͒ technique to the slot-scan and conventional full-field digital radiography techniques for chest imaging. Methods: A prototype SEDR system was designed and constructed with an a-Se flat-panel ͑FP͒ detector to improve image quality in heavily attenuating regions of an anthropomorphic chest phantom. Slot-scanning geometry was used to reject scattered radiation witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 54 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…Tube current modulation (Kalender et al 1999) and the use of bowtie filters (Graham et al 2007, Toth et al 2007 are two common methods used to reduce patient dose, detector dynamic range requirements and x-ray scatter. The positive results of modulating the incident exposure as a function of the imaging object are well-known in two-dimensional projection imaging as well and work was carried out in the 1980's that led to the development of a clinical product capable of dose modulation for different parts of a single radiograph (Plewes 1983, Plewes and Vogelstein 1983, Veldkamp et al 2005, Molloi et al 2001, Liu et al 2011.…”
Section: Introduction: a Short History Of Ffm In Ct Imagingmentioning
confidence: 99%
“…Tube current modulation (Kalender et al 1999) and the use of bowtie filters (Graham et al 2007, Toth et al 2007 are two common methods used to reduce patient dose, detector dynamic range requirements and x-ray scatter. The positive results of modulating the incident exposure as a function of the imaging object are well-known in two-dimensional projection imaging as well and work was carried out in the 1980's that led to the development of a clinical product capable of dose modulation for different parts of a single radiograph (Plewes 1983, Plewes and Vogelstein 1983, Veldkamp et al 2005, Molloi et al 2001, Liu et al 2011.…”
Section: Introduction: a Short History Of Ffm In Ct Imagingmentioning
confidence: 99%
“…This improvement associated with a significant reduction of the average unnecessarily exposed area during image acquisition. Thus, the achieved improvements help to reduce patient dose, but they will also contribute to reduce scattered radiation (26)(27)(28)(29). The optimal collimation in left-right direction also suggests proper centering of the patient in front of the automatic exposure chambers.…”
Section: Discussionmentioning
confidence: 99%
“…Of the several applications, chest X-ray (CXR) is the most indicated for diagnosing pulmonary diseases and viral pneumonia associated with Covid-19 1 . According to studies reported 2 , 44% of all X-ray diagnostic imaging procedures performed in 2006 worldwide were CXR and examination requests are on the increase. Digitization has led to replacement of film-based conventional CXR to digital radiography (DR) and CXR-Computed Tomography (CXR-CT) using flat panel detectors (FPDs).…”
Section: Introductionmentioning
confidence: 99%